THE ROLE OF NON-GOVERNMENTAL ORGANIZATIONS IN THE ECOLOGICAL CULTURE OF YOUTH (Scientific journal of the Fergana State University, 2025)
This article analytically discusses the significant role that non-governmental organizations (NGOs) play in the ecological development of youth. It also provides an explanation of the concept of "non-governmental organization."